Multigravida hamil 35 minggu dengan partus prematurus imminens janin tunggal hidup letak lintang - Fonda Octarianingsih Shariff; Ahmad Murtado (THE JOURNAL OF Mother and Child Health Concerns, 2024)
Abstract A 35-year-old multigravida patient, 35 weeks pregnant, presented to the Emergency Room of RSBAH Bandar Lampung with complaints of leaking amniotic fluid and bloody mucus from the birth canal since 14:00 WIB. The complaints were accompanied by cramps (+). Blood pressure was 120/80 mmHg, pulse 82 beats per minute, respiratory rate 22 breaths per minute, temperature 36.7°C, and oxygen saturation 99%. Hematology findings revealed a decrease in rod leukocytes (1%), an increase in segmented leukocytes (73%), and a decrease in platelets (122.000/μL). Ultrasonography (USG) findings showed a single fetus with a gestational age of 35 weeks and 5 days. The estimated delivery date is November 26, 2024, with an abdominal circumference (AC) of 30.7 cm. The diagnosis in this case is a 35-week pregnant multigravida with imminent premature labor and a single live fetus in transverse lie. The management for this patient includes observation of the general condition, regular TTV checks, and hospitalization with the following treatments: observation of TTV and GCS, advising the mother to rest, IVFD RL + 1-amp Proterin xx tpm, Inj. Dexamethasone 2×2 amps, and Inj. Cefazolin 2×1 g IV. The prognosis in this patient is Dubia ad bonam Keywords: Imminent Preterm Labor; Living Fetus in Lie; Pregnancy. Pasien usia 35 tahun Multigravida hamil 35 minggu datang ke IGD RSBAH Bandar Lampung dengan keluhan keluar air ketuban dan lendir darah dari jalan lahir sejak 14.00 wib. Keluhan disertai mulas (+). Tekanan Darah 120/80 mmHg, Denyut Nadi 82 x/menit, Laju Pernapasan 22 x/menit, Suhu 36,7°C, Saturasi Oksigen 99%. Pada pemeriksaan penunjang hematologi didapatkan Penurunan jenis leukosit batang (1%), peningkatan jenis leukosit segmen (73%), penurunan trombosit (122.000 ul). Pada pemeriksaan penunjang Ultrasonografi (USG) didapatkan kesan Tampak janin tunggal dengan usia kehamilan 35 minggu 5 hari. Perkiraan persalinan pada tanggal 26 November 2024. Abdominal Circumferential (AC) 30,7 cm. Diagnosis pada kasus ini yaitu multigravida hamil 35 minggu dengan Partus Prematurus Imminens Janin Tunggal Hidup Letak Lintang. Tatalaksana yang didapat oleh pasien yaitu observasi keadaan umum, cek TTV secara berkala, indikasi rawat inap dengan pengobatan: Observasi TTV dan GCS, anjurkan ibu untuk bedrest, IVFD RL + 1-amp Proterin xx tpm, Inj. Dexamethasone 2x2 amp, Inj. Cefazoline 2x1 gr/iv. Prognosis pada pasien ini yaitu dubia ad bonam. Kata Kunci: Hamil; Letak Lintang; Partus Prematurus Imminens.